Mutual Interactions between Aquaporins and Membrane Components - Martínez-Ballesta, Maria del Carmen; Carvajal, Micaela (Frontiers in Plant Science, 2016)
During the last years, a number of studies have been focused on the structural evaluation of protein complexes in order to get mechanistic insights into how proteins communicate at the molecular level within the cell. Specific sites of protein-aquaporin interaction have been evaluated and new regulations of aquaporins described based on these associations. Aquaporin isoforms heterotetramerizations are considered as novel regulatory mechanisms for plasma membrane (PIPs) and tonoplast (TIPs) proteins, influencing their intrinsic permeability and trafficking dynamics in the adaptive response to changing environmental conditions. However, protein-protein interaction is an extensive theme that is difficult to tackle and new methodologies of physical interactions are being used in approaches to its study. Bimolecular fluorescence complementation (BiFC) and the identification of cross-linked peptides based on tandem mass spectra, which resulted complementary to other methodologies such as heterologous expression, co-precipitation assays or confocal fluorescence microscopy, have been discussed in this review. The chemical composition or physical characteristics of the lipid bilayer also influences many aspects of membrane aquaporins, including their functionality. The molecular driving forces stabilizing the observed lipid positions around aquaporins could define their activity, which could alter the conformational properties. Therefore, an integrative approach to the relevance of the membrane-aquaporin interaction to different processes related to plant cell physiology is shown. Finally, the interactions between aquaporins and copolymer matrixes or biological compounds offer an opportunity for the functional incorporation of aquaporins into new biotechnological advances.